The Effects of Playing Playdough on the Ability to Recognize Geometric Shapes in Kindergarten - Tantri Ardianti; Budi Purwoko; Umi Anugerah Izzati (Studies in Philosophy of Science and Education, 2023)
The ability to recognize geometric shapes is still lacking, such as children who have not been able to classify objects based on shape, color, and color pattern. This study uses a quantitative approach with a quasi-experimental design. The experimental design used was a nonequivalent control group design with 32 children as research subjects carried out at RA Ashyubbani Changing. this study used parametric statistical data analysis techniques using the ANOVA test. The conclusions of this study indicate that there is an effect of playing with plasticine on the ability to recognize geometric shapes in group A Kindergarten. The results showed a correlation coefficient 0.526 with a significance level of 0.006 which is less than 5%; this shows that there is an effect of playing with plasticine on the ability to recognize geometric shapes in group A kindergarten children. Playdough activities can improve children's abilities to recognize geometric shapes both in grouping objects based on shape, color, and color pattern.